The modern history of Oman In Russian published sources 1824 - 1920 (Journal of the College of Basic Education, 2022)
Our research came as a modest attempt to reveal the modern history of Oman from the beginning of the sixteenth century until the outbreak of the First World War, by referring to some Russian sources between published documentaries, Arabic books and books, as well as research published in periodicals, to bring what is new about Oman's political situation Economic and geographical, which may give us information that is added to what is available in Arab and foreign sources about Oman, and may shed light on an aspect that is unknown, or that is lacking in texts that allow us to study some of Oman’s modern history.Perhaps this study will be a little far from the path of academic research, as it relied in most of its contents on what Russian sources wrote about the observations of Russian travelers and trade.